2019
DOI: 10.3390/ijms20174173
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymeric Films of Amphiphilic Derivatives of Chitosan: A Physicochemical Characterization and Antifungal Study

Abstract: The chemical modification of chitosan has been an active subject of research in order to improve the physicochemical and antifungal properties of chitosan-based films. The aim of this study was to evaluate the physiochemical and antifungal properties of films prepared with chitosan and its derivatives containing diethylaminoethyl (DEAE) and dodecyl groups (Dod). Chitosans and selected derivatives were synthesized and characterized, and their films blended with glycerol and sorbitol (5%, 10%, and 20%). They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The absorbance measurements at 600 nm for Cs–DEAE showed values close to 0.0 in pH conditions under 8.3, without the appearance of precipitates until the solution was adjusted to pH = 11.3 (absorbance 600 nm = 0.20). The highest water solubility of Cs–DEAE is attributable to the contribution of the p K a ∼ 10.0 of the tertiary amino group of DEAE . On the other hand, it is observed that the Cs–DC solutions only slightly increase their absorbance at 600 nm to ∼0.06, even at pH = 11.3.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The absorbance measurements at 600 nm for Cs–DEAE showed values close to 0.0 in pH conditions under 8.3, without the appearance of precipitates until the solution was adjusted to pH = 11.3 (absorbance 600 nm = 0.20). The highest water solubility of Cs–DEAE is attributable to the contribution of the p K a ∼ 10.0 of the tertiary amino group of DEAE . On the other hand, it is observed that the Cs–DC solutions only slightly increase their absorbance at 600 nm to ∼0.06, even at pH = 11.3.…”
Section: Resultsmentioning
confidence: 94%
“…Cs–Ca and Cs–DC conjugates were synthesized using EDC coupling chemistry by forming amide bonds between a primary amine group in Cs or Cs–DEAE and a carboxylic acid group in HCA . Since the EDC chemistry is more propitious for the non-protonated amino groups, the conjugation took place at pH 5.5 to prevent the precipitation of the Cs (p K a = 6.2–6.4) and limit amino protonation . It is important to note that the incorporation of specific chemical groups can increase the polymer’s solubility at a higher pH range compared to the unmodified Cs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by work on protective polymeric films for the coating of plant seeds [ 11 , 12 , 13 ], we envisaged a novel strategy to tackle fungal skin infections by using film-forming agents. These are typically polymers that can form a continuous thin layer on biotic or abiotic surfaces.…”
Section: Introductionmentioning
confidence: 99%